Pengaruh Kepribadian Konsumen pada Pilihan Merek sebagai Konsep Diri pada Kategori Produk - Wardana, Dwiyadi Surya (Jurnal Ilmiah Aset, 2011)
This research was conducted to see the influence of consumer personality on brand selection as a self-concept on automobile product category. Avanza, Xenia, Jazz, Innova and Rush are the brand of cars that becomes an object of research. In this research consumer personality consists of four variables and brand personality as selfconcept consists of two variables. Data was collected by using survey method, and thevalidity test for items of questionnnaire using factor analysis. Then to see the influence of consumer personality on brand selection as a self-concept on automobile product category this study used multiple regression analysis. Anova analysis was used to test every car owner in the notice of a difference in consumer personality and brand personality as a self-concept. The empirical results, in this study a statistical test showed that consumers used their personality to select the brand identity that match with the concept itself.